MESH STRESS AND FATIGUE LIFE STUDY OF WALKING MECHANISM OF SHEARER UNDER PRACTICAL WORKING CONDITIONS - CHEN HongYue; JIAO SiWei; ZHANG Kun; MAO Jun (Jixie qiangdu, 2018)
In order to reveal the damage mechanism in the working process of the traveling mechanism of shearer,establishing dynamic contact model of walking mechanism in LS-DYNA. By using the experimentally measured traction resistance and gravity of shearer as external load,transient dynamic simulation was executed.The rain flow count、load extrapolation and superposition of dangerous nodes maximum equivalent stress time history were conducted by using Rain-flow module in the n-code GlypWorks. Fatigue life of walking wheel and pin rows were calculated by using Stress Life module of n-code GlypWorks. The results show that: walking mechanism of shearer have good mechanical properties. Minimum fatigue life of walking wheel is 307 days, and minimum fatigue life of pin row is 323 days.The results provide theoretical basis for structure optimization of traveling mechanism.